The Ability of A Consortium of Cellulose-Degrading Bacteria In Fixing Nitrogen, Dissolving Phosphorus and Potassium, and Its Application As A Bifertilizer In Tomato Plants - Sigit Mawardi; Hadi Susilo; Suyamto Suyamto (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
This study aims to determine the ability of cellulose-degrading bacteria to fix nitrogen, dissolve phosphorus and potassium, and assess their effectiveness as biofertilizers for tomato plants. The research method used is quantitative descriptive, involving in-vitro testing and field application with two treatments: P0 (without bacteria) and P1 (with bacteria). The results of this study indicate that cellulose-degrading bacteria possess additional capabilities in nitrogen fixation, as evidenced by a color change in the NFB medium to blue, and demonstrate the ability to solubilize phosphorus and potassium, as indicated by the formation of clear zones in the Pikovskaya and Alexandrov media. Field testing showed that cellulose-degrading bacteria were effective in tomato plants, influencing plant height parameters but not affecting leaf area or number of leaves. Based on the results of the Two-Way ANOVA analysis on the treatments conducted, there was no significant effect, as the P-value was >0.005. Cellulose-degrading bacteria in vitro have the ability to provide nutrients. However, they are not yet effective in enhancing the vegetative growth of tomato plants.